Marketing Strategy for Mudharabah Savings (Tabah) Products in Increasing the Number of Customers at the KSPP Syariah BMT NU East Java Leces Branch - Yeni Kartikawati; Siti Amina (Formosa Journal of Science and Technology, 2023)
The purpose of this study was to find out how the marketing strategy for mudharabah (Tabah) savings product was carried out by KSPP Syariah BMT NU Jawa Timur Cabang Leces Probolinggo increased the number of customers. Data collections methods used are observation and interview. In this study it can be concluded that in marketing savings products the intial action is knowing the situation so that you can know what steps will be taken. Best on the findings of the data, that the marketing strategy for mudharabah (Tabah) saving products in increasing the number of customers at the BMT NU JATIM Cabang Leces Probolinggo institution used the 7P&1C marketing mix that is product, price, place, promotion, people, process, physical evidence, and customer service.